Ekonomia polityczna a demokracja w pismach klasyków liberalizmu – John Stuart Mill i Herbert Spencer (Politeja, 2023)
POLITICAL ECONOMY AND DEMOCRACY IN THE WRITINGS OF CLASSICAL LIBERALS – JOHN STUART MILL AND HERBERT SPENCERThe main aim of this paper is showing mainstream  economic theory as an important factor shaping the evolution of political liberalism. The role of the economic theory in this process seems underestimated. The paper analyses the writings of two classical liberal thinkers – John Stuart Mill and Herbert Spencer, the former a pioneer of egalitarian liberalism, the latter of laissez-faire liberalism. Both Mill and Spencer were the followers of the classical political economy accepting the classical theory of distribution. Both saw the distribution of wealth as a spontaneous process, seeing no possibility correcting it for the people’s sake without disturbances or damages. According to the classical theory of wage fund, workers would get higher incomes only through accumulation of capital by owners and repressing their own fertility. Such statement was fundamentally opposite to all postulates of the workers’ movement. Workers always claimed bigger share in social income and legislation favoring laborers. The inevitable result of this contradiction was a conflict between liberal and democratic ideas. Mill and Spencer proposed two different solutions. J. S. Mill found a specific compromise and proposed enlarging franchise on working class, but with a still dominant position of the educated classes. Mill was against equal franchise for the working class because he did not conceive them as liable, rational and sober people. This position results from the wage fund doctrine; according to it, abundant workers’ fertility is wasteful for them and only sexual restraint (or chastity) would make their wages higher. Spencer in his early writing was an enthusiast of democracy, supposing the working class’ affinity to free market solutions. His later disappointment with democracy turned him into a strong critic of democratic parliamentarism from the standpoint of laissez-faire individualism. The case of these two liberal thinkers shows fundamental difficulty in reconciliation between the ideas of democracy and free market. We could choose democracy accepting welfare state or choose free market solution and become unambiguous critics of democracy. Spencer was a forerunner of all later ‘neoliberal’ critics of welfare state. Mill’s opinion was halfway between laissez-faire liberalism and modern egalitarian liberalism. Democracy and equal voting rights became acceptable by mainstream economist only when they had abandoned the wage fund doctrine and other constructs of the classical political economy. Thus changes in the economic theory had a significant impact on the evolution of political liberalism.